The death of Luigi Trastulli, and other stories : form and meaning in oral history - Portelli, Alessandro (SUNY series in oral and public history., 1991)
Portelli offers a new and challenging approach to oral history, with an interdisciplinary and multicultural perspective. Examining cultural conflict and communication between social groups and classes in industrial societies, he identifies the way individuals strive to create memories in order to make sense of their lives, and evaluates the impact of the fieldwork experience on the consciousness of the researcher. By recovering the value of the story-telling experience, Portelli's work makes delightful reading for the specialist and non-specialist alike.